E-Retailing in India: Boon or Bane for Customers - Devi , Suman (International Journal of Psychosocial Rehabilitation, 2020)
by 2025, up from 622 million in 2020, with a CAGR of 45 percent between 2020 and 2025. To avoid crowds during difficult times, everyone turned to online shopping. The primary goal of this study is to provide a strategic analysis of key online retailers in India, including market share, funding, obstacles, and consumer convenience. This study also conducts a SWOT analysis of the click-and-mortar retail model in India, identifying the elements that influence the expansion of the virtual retail industry, as well as the primary factors impacting the online retail company.